Prospects for studies related to teacher identity: a state of the art (2019)
This work is based on a review of research and theoretical reflections in Iberoamerica, from 2000 to 2014, about teacher professional identity and narrative. In this examination, a summary of the most relevant works, organized around four thematic stems: relation between identity, narrative and education; aspects, factors or processes considered in shaping the narrative and professional identity of the teacher; public policies in education and its relation to the identity of the teacher; and relevant aspects considered the biographical-narrative approach from a methodological. Additionally, a graphical display of the type of documents reviewed, according to their origin country, questions or concerns frequently, and the type of research results is made.